2023
DOI: 10.1097/rhu.0000000000001935
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Women With Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory rheumatic disease affecting multiple joints and can also be a systemic widespread, affecting major organs. Rheumatoid arthritis is associated with greater adverse maternal and neonatal outcomes in comparison to the general obstetric population. This systematic review and meta-analysis aims to investigate the pregnancy outcomes in RA patients in comparison to the general pregnant population.Nine studies involving 11,999 RA patients met the eligibility criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(214 reference statements)
2
10
0
Order By: Relevance
“…Our study also had several findings that have been similarly reported in other studies on this population: patients with RA/JIA in our study have higher rates of C-sections and pre-eclampsia; 6,26,28,35 however the rates of stillborn are the same as individuals without RA/JIA. 6 From our mediation analysis, we found that PEC accounted for only about 4% of fetal growth restriction.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our study also had several findings that have been similarly reported in other studies on this population: patients with RA/JIA in our study have higher rates of C-sections and pre-eclampsia; 6,26,28,35 however the rates of stillborn are the same as individuals without RA/JIA. 6 From our mediation analysis, we found that PEC accounted for only about 4% of fetal growth restriction.…”
Section: Resultssupporting
confidence: 90%
“…Our results are consistent with prior studies on pregnancy outcomes among patients with RA/JIA: pregnant patients with RA tend to be older at the time of pregnancy, at higher risk for hypertensive disorders during pregnancy, tend to undergo C-section deliveries, and their offspring are likelier to have restricted fetal growth. 2,15,26 Interestingly, our study found that patients with RA/JIA who used CS or SSZ during pregnancy had higher EFW during the second trimester compared to fetuses of patients without RA/JIA (Table S3). As patients with RA/JIA are at higher risk of early pregnancy losses and subfertility, 27,28 it is plausible that the finding of higher EFW during second trimester among women with RA/JIA was influenced by survivor bias.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Pregnancy is an inevitable issue for WCBA at adult stage, and maternal mortality caused by severe pregnancy complications in this population inhibits the realisation of sustainable development goals established by the United Nations. Compared with the general obstetric population, pregnant women with MSK disorders have higher risk in developing adverse maternal, neonatal and fetal outcomes including gestational hypertension, pre-eclampsia, caesarean delivery, preterm delivery, low birth weight, congenital anomalies, stillborn, etc ,29 30 which may be associated with medication use and disease activity 30. Moreover, the flare of MSK disorders may coexist with these complications, and difficulties in differential diagnosis are raised 31.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticosteroids are one of the medications commonly used in pregnancy to control IRD disease activity, given that a large number of classical and biologic DMARDs cannot be used due to their teratogenicity and ability to cross the placenta. It was demonstrated in some studies that long-term GC use during pregnancy can be associated with an increased risk of gestational hypertension, pre-eclampsia, and gestational diabetes [61,62]. The use of PDN during pregnancy has been found to increase the risk of premature delivery and, consequently, lower birth weight in pregnant women with RA.…”
Section: The Drawbacks Of Glucocorticosteroids In Treating Inflammato...mentioning
confidence: 99%